Factors influencing job satisfaction among expatriate working in Johor / Muhammad Fahimy Irsyadudin Saleh and Farahnaz Sarina Muhamad Salleh - Saleh, Muhammad Fahimy Irsyadudin; Muhamad Salleh, Farahnaz Sarina (Faculty of Business and Management, 2013)
This research entitles “Factors Influencing Job Satisfaction among Expatriate Working in Johor”. Job satisfaction among expatriate slowly has become major concern issues by many organization because it will be one of determinants on work performance in an organization. Job satisfaction in more simple way can define as the extent to which people like (satisfaction) or dislike (dissatisfaction) towards their jobs. It shows that level of job satisfaction of one employee is general or global effective reaction when he holds his job. Individual’s job satisfaction comes from how he or she feels is more important than fulfillment of his or her needs or not. Only they know level of job satisfaction among themselves and an organization should play its role to prepare and serve as much as it can to fulfill employees’ needs. Several determinants of job satisfaction that can consider by an organization such as organizational reward systems, power distribution, individual differences, self-esteem and focus of control. We decided to conduct this research in the area of Johor because it is one of the state that have potential to contribute more to growth and economic of Malaysia. The objective of this research is to find out the relationship of job satisfaction among expatriate working in Johor and its factors which are pay and promotion, organization aspect, supervisors, job and working condition and co-worker. The respondents of this research are expatriates working in Johor. In order to complete the research and get feedback from respondent, 70 questionnaires were distributed in the area of Johor. All the findings of this research will show the relationship of each variable on job satisfaction.